Certificações voltadas para edificação civil: análise comparativa entre o modelo de certificação Selo Verde, implantado em uma empresa de mineração e a certificação LEED - Costa, Karinelle Lima de Figueirêdo Gomes (2016)
The growing interest and awareness of the issue of sustainability within companies led to the creation of an environmental certification of buildings with its own methodology within the mining sector. The increased interest gave rise a new situation, characterized in analyzing the representativeness of this front methodology to an international methodology. Certifications or Green Seals are tools used to aver if sustainable buildings have acceptable performance levels through energy efficiency, reducing the use of natural resources and generation of pollution, confirming good management of the environment built. The present study was aimed to promote comparative analysis of methodologies and requirements applied for SELO VERDE, own methodology implemented in a mining company and LEED certification, seeking opportunities for improvement and adaptation possibilities to support for environmental certification of sustainable buildings. The methodology used was divided into classification stages of certification systems defined to work, comparative analysis between selected environmental certification systems and discussing about inadequacies and proposition of alternatives for adaptation of such evaluative criteria for the context of the buildings found in the mining company. From the comparative analysis and marking of the evaluation items, it can be said that the tools and credits studied demonstrated to be applied for the buildings located within the company even if improvements are necessary for some items. This consolidated by PROPOSED SELO VERDE.